2014
DOI: 10.1542/peds.2013-2621
|View full text |Cite
|
Sign up to set email alerts
|

Peer Mentoring for Type 2 Diabetes Prevention in First Nations Children

Abstract: OBJECTIVE: The goal of this study was to assess the efficacy of an after-school, peer-led, healthy living program on adiposity, self-efficacy, and knowledge of healthy living behaviors in children living in a remote isolated First Nation. METHODS: A quasi-experimental trial with a parallel nonequivalent control arm was performed with 151 children in Garden Hill First Nation during the 2010–2011 and 2011–2012 school years. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 28 publications
2
66
1
Order By: Relevance
“…175186 Table 2 shows that peer mentoring efforts have demonstrated improvements in quality of life, 187189 adherence, 191193 self-management 194198 and disease activity 197,198 in a variety of conditions. For example, peer support has been shown in patients with diabetes mellitus (DM) to improve medication adherence, diet, exercise and blood glucose monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…175186 Table 2 shows that peer mentoring efforts have demonstrated improvements in quality of life, 187189 adherence, 191193 self-management 194198 and disease activity 197,198 in a variety of conditions. For example, peer support has been shown in patients with diabetes mellitus (DM) to improve medication adherence, diet, exercise and blood glucose monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Six of 10 studies that reported a weight‐related measure as a primary outcome reported significant improvements. Three studies, including one 5‐month and two 10‐month interventions, reported significant decreases on measured body mass index (BMI) or BMI z ‐score . Also, one study each reported significant decreases in percent overweight or obese (at 11 months) , waist circumference (at 10 months) and weight (at 12 weeks) .…”
Section: Resultsmentioning
confidence: 99%
“…Among interventions that used a functional participatory approach, nine indicated that adult research team members, specialized trainers or school teachers provided training on curricula or specific approaches such as motivational interviewing. The studies provided limited details about the frequency or duration of the training sessions (28)(29)(30)(31)36,(39)(40)(41)(42). Of studies that did provide frequency and duration details, training ranged from 3 to 40 h (27, 37,38,43).…”
Section: Identification and Training Of Children And Youth For Particmentioning
confidence: 99%
“…No difference was found between the community health worker group and the parent mentor group. The internal consistency of the data is reinforced by the finding that those above the self-efficacy median even despite the overall high scores were more likely to report higher confidence in making a behavioral change such as making healthier choices, finding resources, and believing that their child can achieve a healthy weight [24]. …”
Section: Discussionmentioning
confidence: 99%